Prognostic Factors for COVID-19 Pneumonia among Pregnant Women with COVID-19 Infection - Yukaew, Nitiporn (Journal of Preventive Medicine Association of Thailand, 2023)
Coronavirus disease 2019 (COVID-19) is a global ongoing pandemic disease. Pregnant women more likely to get severely ill from COVID-19 compared to the general population. This retrospective cohort study aimed to analyze prognostic factors for COVID-19 pneumonia in pregnant women with COVID-19. This study was conducted in a total of 126 pregnant women with COVID-19. Data were analyzed by frequency, percentage, mean and standard deviation. The multiple logistic regression analysis was used to determine the prognostic factors for COVID-19 pneumonia. Results: After exclusion of 23 cases due to lack of chest x-ray imaging, we found 44.7% of COVID-19 pneumonia in 103 pregnant women. The disease severity in most of patients were not severe. The most common clinical manifestations of COVID-19 in pregnancy were fever and upper respiratory infection symptoms. COVID-19 pregnant women with fever developed more pneumonia 1.55 times compared to covid-19 pregnant women without fever. COVID-19 pregnant women with fever on admission, temperature 37.5-38.4°C developed more pneumonia 3.16 times compared to covid-19 pregnant women without fever. COVID-19 pregnant women with high fever on admission, ≥ 38.5°C developed more pneumonia 5.35 times compared to covid-19 pregnant women without fever. Conclusion: Prognostic factors of COVID-19 pneumonia in pregnant women with COVID-19 are history of fever and fever on admission. COVID-19 pregnant women with fever should be monitored, get further investigation such as chest x-ray imaging and medication consideration based on benefits over risks that make care more efficient.